C-Breeze smart collar / Luqman Hariz Shaarani, Muhammad Luqman Ismadi and Damia Kamilia Ahmad - SHAARANI, LUQMAN HARIZ; ISMADI, MUHAMMAD LUQMAN; AHMAD, DAMIA KAMILIA (2018)
The team is developing a product, C-Breeze, which is an air conditioner infused ina smart collar. C-BREEZE is a collar-cum-air-conditioning device used by attaching thedevice at the back of the neck for instant cooling. Conditioned air will be distributed throughfins cooling parts of the body including the face area, the back of the body and the upperchest area. The C-BREEZE will also pre-functions as a neck massaging device and a scentemitter.